1985
DOI: 10.1029/ja090ia11p10875
|View full text |Cite
|
Sign up to set email alerts
|

An ISEE 3 study of average and substorm conditions in the distant magnetotail

Abstract: Average and substorm conditions in the lobe and plasma sheet regions of the earth's magnetotail are studied as a function of downstream distance and east‐west location using ISEE 3 magnetometer and plasma analyzer measurements. On the basis of 756 magnetopause crossings a low‐latitude magnetotail diameter of 60±5 RE at |X| = 130 ‐ 225 RE is determined. The strength of the lobe magnetic field from |X| = 20 to 130 RE is shown to fall off as X−0.53±0.05. Flaring ceases on average at |X| = 120 ± 10 RE with a relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

34
240
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 326 publications
(275 citation statements)
references
References 93 publications
34
240
1
Order By: Relevance
“…In reality, the region of acceleration may be some distance from the observation site. Slavin et al [1985] have described the change in lobe density and magnetic field with respect to downtail distance. They find that in the region X > -100 RE, the lobe density increases with downtail distance, as the plasma mantle fills in the lobes, while the magnetic field strength decreases.…”
Section: Resultsmentioning
confidence: 99%
“…In reality, the region of acceleration may be some distance from the observation site. Slavin et al [1985] have described the change in lobe density and magnetic field with respect to downtail distance. They find that in the region X > -100 RE, the lobe density increases with downtail distance, as the plasma mantle fills in the lobes, while the magnetic field strength decreases.…”
Section: Resultsmentioning
confidence: 99%
“…[33] The model has not explicitly addressed the issue of closed field line regions sometimes observed in the flanks of the magnetotail at distances of a few hundred R E [e.g., Slavin et al, 1985]; it has been suggested that these are associated with a curved distant X-line [Slavin et al, 1985] or are nearEarth flank field lines which have been carried downtail by diffusive momentum transfer from the magnetosheath [e.g., Mist and Owen, 2002]. We offer an alternative interpretation, noting that draped c+ open field lines produced by lobe reconnection will coat the flanks of the tail with regions of B z -positive magnetic field, which could be misinterpreted as closed field lines if viewed in the equatorial plane.…”
Section: Discussionmentioning
confidence: 99%
“…The transport of open flux from the dayside to the nightside owing to the antisunward flow of the solar wind is now known as the Dungey convection cycle [Dungey, 1961[Dungey, , 1963 and results in the formation of a magnetotail of length $1000 R E [Dungey, 1965]. There is also a ''disconnected'' tail, which comprises the highly kinked solar wind field lines newly reconnected at C. It is now thought that reconnection can take place at two locations in the magnetotail: at a ''distant'' X-line $150 R E downtail during quiet times [e.g., Slavin et al, 1985], and a ''near-Earth'' X-line during substorms near 20-30 R E [e.g., Siscoe and Cummings, 1969;McPherron et al, 1973;Russell and McPherron, 1973]. The only tail X-line that is of importance to this study is the one that is actively reconnecting open lobe field lines, and in the rest of this paper tail reconnection is considered as a single process.…”
Section: Magnetotail Modelmentioning
confidence: 99%
“…It is also generally assumed, that reconnection of lobe field lines occurs at almost any time. During geomagnetically quiet times, reconnection is believed to occur in the distant tail at an X-line that is located around 100 RE from earth [Slavin et al, 1985], while during geomagnetically active times, one or more X-lines develop closer to earth, leading to the formation of plasmoids or flux ropes that are ejected through the distant tail [Hones, 1979]. The models predict that convection associated with the reconnection sites is generally earthward on the earthward side of an X-line and tailward on the tailward side [Dungey, 1961;Cowley, 1980].…”
Section: Introductionmentioning
confidence: 99%